If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -5 = -2 + 14 Reorder the terms: -5 + 3n = -2 + 14 Combine like terms: -2 + 14 = 12 -5 + 3n = 12 Solving -5 + 3n = 12 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3n = 12 + 5 Combine like terms: -5 + 5 = 0 0 + 3n = 12 + 5 3n = 12 + 5 Combine like terms: 12 + 5 = 17 3n = 17 Divide each side by '3'. n = 5.666666667 Simplifying n = 5.666666667
| 4+(-11)=5x-7-4x | | 2a-5=8n+7 | | -.83x+27=-23 | | 75=-5[a+5] | | 8(v+2)-2v=2(3v+2)-7 | | 2(5n-4)+9n= | | 0=12x+22 | | e/9=3 | | 17x-22x=1/3 | | -.16(x-12)+.33(x+3)=x+8 | | 5g+9=2g+3 | | (1/2)x-(3/5)y=5 | | -10y=68-2(4-2y) | | 2x^5+6x^3+4x=0 | | 16p^6q^4+32p^5q^3-48pq^2= | | -x^3+9x+2=0 | | -3(6s+2)= | | r^2+7r-18= | | -2(2y-1)+2y=4(y+4) | | -2(u+2)=7u-1+3(3u+1) | | -.16(x-12)+.5(x+2)=x-1 | | 3(9x-8)=2(4x+2) | | 72x-89=x-81 | | (2*4y)+(2*5y)=0 | | (3z+2)(4-z)=0 | | 15+10x=13x | | 10(X)=X-7 | | 4(8n-3)+7n= | | G-2/7=6 | | 4(r+1)= | | 0=-5x^2+3x^2 | | 4+4(3x-2)=-2(4x-6)+8x |